Influence of cavity depth and restoration of non-carious cervical root lesions on strain distribution from various loading sites - Je-Kang Du; Ju-Hui Wu; Ping-Ho Chen; Pei-Shan Ho; Ker-Kong Chen (BMC, 2020)
Abstract Background We aimed to investigate the load-induced strain variation in teeth with unrestored and resin-based composite restored non-carious cervical lesions (NCCLs). Methods Twelve extracted premolars were provided for measuring buccal-side root NCCLs. Strain gauges were fixed at four measuring sites of each tooth, two at the buccal surface and two at the lingual surface. NCCLs were prepared with occlusal margins at the cemento-enamel junction. A static 9-kg load was applied at seven occlusal loading points: buccal cusp tip (BC), inner inclination of the BC, lingual cusp tip (LC), inner inclination of the LC, center of the mesial marginal ridge or distal marginal ridge, and center of the central groove. The strain was detected at each site in teeth with NCCL depths of 0 (control), 0.5, 1.0, and 1.5 mm. Each NCCL was restored using an adhesive composite resin, and the strains were re-measured. Results The strains at the NCCL occlusal and gingival margins decreased with increasing defect depths, and the effect was significant when the depth of the defect was 1.5 mm. Loading on the buccal and lingual cusps induced prominent strain variation. The strains at all depth distribution recovered to nearly intact conditions when the NCCLs were restored. Conclusions NCCLs at 1.5 mm depth are detrimental, but they can be restored using resin composites. Clinical significance The existence of NCCLs should not be ignored. The depth of the NCCL may affect the progression of the lesion. Resin composite restoration is an appropriate method for preventing persistent NCCL deterioration.